Transformation & trouble: crime, justice, and participation in democratic South Africa - Gordon, Diana R. (University of Michigan Press, 2006)
Introduction : two paradigms and a program -- Pre-apartheid justice : versatile instrument of repression -- Apartheid justice : a contradiction in terms -- Bitter fruit from poison seeds -- Elements of liberal justice in a new democracy -- Protection, integrity, and rights : South African achievements -- Public-empowering justice : resource for a new democracy -- Participation thwarted : South African failures -- Wielding the big stick -- Democratic justice and the competent citizen.